The in situ Production of Aquatic Fluorescent Organic Matter in a Simulated Freshwater Laboratory Model - Perrin, Eva M.; Thorn, Robin M. S.; Sargeant, Stephanie L.; Attridge, John W.; Reynolds, Darren M. (Frontiers in Microbiology, 2022)
Dissolved organic matter (DOM) is ubiquitous throughout aquatic systems. Aquatic fluorescent organic matter (AFOM) has characteristics associated with microbially-derived DOM (conventionally identified as Peak T) or terrestrially-derived DOM (conventionally identified as Peak C/C+), with Peak T previously being investigated as a tool for bacterial enumeration within freshwaters. The impact of anthropogenic nutrient loading on the processing of DOM by microbial communities is largely unknown. Previous laboratory studies utilizing environmental freshwater have been limited by complex fluorescence and nutrient matrices. We describe a laboratory-based model with Pseudomonas aeruginosa, that incorporates a non-fluorescent simulated freshwater matrix allowing controlled nutrient conditions to be studied. The effects of microbial processing of DOM as a function of available nitrogen, phosphorous and dissolved organic carbon (DOC) were investigated over 48 hours at highly resolved time increments. The model demonstrates the production of a range of complex AFOM peaks in the presence and absence of DOC, revealing no linear relationship between cell numbers and any of the peaks for the bacterial species studied, with AFOM peaks increasing with microbial replication and growth, ranging from 50 quinine sulphate units (QSU) per 106 cells to 290 QSU per 106 cells (p < 0.05) during the exponential growth phase (condition dependent) of the microbial community. Nutrient and DOC availability was found to cause differential production of autochthonous- or allochthonous-like AFOM, with lower DOC concentrations resulting in higher Peak T production relative to Peaks C/C+ upon the addition of nutrients, and high DOC concentrations resulting in higher Peak C/C+ production relative to Peak T. Our results show the production of allochthonous-like AFOM from a simple and non-fluorescent carbon source, and provide uncertainty in the use of Peak T as a reliable surrogate for specific bacterial enumeration, particularly in dynamic or nutrient-impacted environments, pointing towards the use of fluorescence as an indicator for microbial metabolism.